Preparation of transversely isotropic test specimen of natural FRP composite - an innovative approach-II - A, Srihari Prasad; V, Balakrishna Murthy; V, Ramana K; G, Sambasiva Rao (Journal of Experimental Sciences, 2012)
Fiber Reinforced Plastic (FRP) composites can be broadly classified as synthetic and natural, based on the type of fibers incorporated. Abundantly available natural fibers like toddy palm, sisal, jute and banana are attracting the attention of researchers due to ever increasing demand for lighter, stronger and eco-friendly materials from the industry. However, natural fibers are limited in length, not so uniform in size and behave differently in different atmospheric conditions. Added to this, the inherent tendency of natural fibers to twist and curl in dry conditions poses many problems to researchers while preparing test specimens. Researchers in general and academicians in particular are handicapped by non-availability of relevant literature on fabrication techniques to prepare natural FRP composite test specimens close to their analytical models. Present paper addresses typical problems faced by researchers during preparation of unidirectional continuous fiber reinforced composite test specimen ensuring transversely isotropic nature. Using simple hand tools coupled with a few precautions taken as described herein, prospective researchers can condition natural fibers and prepare composite specimen to suit their requirements.